2004
DOI: 10.1124/dmd.104.001693
|View full text |Cite
|
Sign up to set email alerts
|

Malathion Bioactivation in the Human Liver: The Contribution of Different Cytochrome P450 Isoforms

Abstract: ABSTRACT:Among organophosphorothioate (OPT) pesticides, malathion is considered relatively safe for use in mammals. Its rapid degradation by carboxylesterases competes with the cytochrome P450 (P450)-catalyzed formation of malaoxon, the toxic metabolite. However, impurities in commercial formulations are potent inhibitors of carboxylesterase, allowing a dramatic increase in malaoxon formation. Malathion desulfuration has been characterized in human liver microsomes (HLMs) with a method based on acetylcholinest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 36 publications
3
67
1
Order By: Relevance
“…In humans, the production of malaoxon from malathion has been shown due to an enzyme in the liver microsome. 13) However, monooxygenase activity and malaoxon residue have not been detected in wheat kernels containing malathion residue. 16,17) Our results support the previous reports showing that monooxygenase does not contribute to the elimination of malathion residue in wheat kernels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the production of malaoxon from malathion has been shown due to an enzyme in the liver microsome. 13) However, monooxygenase activity and malaoxon residue have not been detected in wheat kernels containing malathion residue. 16,17) Our results support the previous reports showing that monooxygenase does not contribute to the elimination of malathion residue in wheat kernels.…”
Section: Discussionmentioning
confidence: 99%
“…thiomalate, malathion monocarboxylic acid, and desmethyl malathion were shown to be produced by monooxygenase, 2,13) organophosphorus hydrolase, 7) carboxylesterase, 6,8,10,12) and methyltransferase, 11) respectively. Mostafa et al estimated that the degradation of malathion sprayed on cotton and broad beans in field experiments was mainly caused by the carboxylesterases in the crops, judging from the formation of malathion monocarboxylic acid.…”
Section: Malathion Residue In Wheat Kernels Is Degraded By Thion Orgamentioning
confidence: 99%
“…Malathion is an organophosphorothionate pesticide with relative low toxicity, can be activated by the cytochrome P450 system by oxidative desulfuration to form malaoxon, an effective inhibitor of AchE. 23 In the present study, we have explored the effects of a sub chronic exposure of malathion at 27mg/kg bw (1/50 of the oral LD 50 ) for 90days on liver and kidneys toxicities in male rats. Present study showed that sub chronic exposure to malathion was able to induce a significant decrease in body weight, food intake, liver and kidney weights in ML-treated group compared control group.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomal mixed function oxidase is the primary enzyme for the phase I reactions that convert xenobiotics into more soluble products. Although these products are generally less toxic than the parent compound, more toxic metabolites may also occur, as in the cases of parathion (Chambers et al, 1991) and malathion (Buratti et al, 2005). Such in vitro studies with microsomal preparations provide specific details of the chemical identity of metabolites and intermediates, the pattern of their formation, and the metabolic pathways of xenobiotics (Liu et al, 2002;Liu and Kim, 2003;Kim et al, 2005a).…”
mentioning
confidence: 99%